Construção e validação de cartilha educativa para prevenção de quedas em idosos - Alves, Allana Mirella (2017)
Elderly are more prone to fall due to changes in functional reserve and due to exposure to several risk factors for many years. In view of the importance of this problem of public health, basic safety and prevention care measures should be taken. The aim of this work is to develop and to validate an educational guidebook for the prevention of elderly fall. This methodological study was carried out from March 2015 to September 2016. The following steps were applied: situational diagnosis with 15 elderly woman of VIDA group, literature review, guidebook elaboration, material validation by 30 judges, evaluation of the suitability of the material through SAM (Suitability Assessment of Materials), calculation of Flesch readability index and pilot experiment with 40 community elderly. The Health Belief Model was used as basis to elaborate the guidebook. Workshops with elderly were carried out to collect information about falls. The following topics were noted: balance, fear of falling, stand up at night, visual deficit, stairs, carpets, slippery/wet floor, walking animals through the house, bed and hammock height, inadequate house infrastructure, insufficient financial condition, polypharmacy and not adapted bathroom. In the bibliographical review, publications that consider the variables of the Health Beliefs Model (susceptibility, severity, benefits and perceived barriers) were included. Nineteen publications were selected. The guidebook was elaborated based on the workshops and a designer was consulted to make the figures. Thirty judges were selected to evaluate the content and the guidebook appearance according to pre-established criteria. An excellent agreement between the replies was observed and the guidebook was validated with an overall Content Validity Index of 96% agreement between responses. The SAM evaluated the guidebook as excellent or superior with general index of 90.9%, classifying the material as superior and recommending its use by the intended audience. Flesch readability indexes ranged from 71 to 82.5%, classifying the material as reasonably easy, easy or very easy and as acceptable for the schooling of the elderly. Lastly, the pilot experiment showed that 100% of the 40 respondents rated the developed guidebook as good, great or excellent.